E-office for UiTM : a survey analysis / Nalini Dharmarajan, Anitawati Mohd Lokman and Zarina Zainol - Dharmarajan, Nalini; Mohd Lokman, Anitawati; Zainol, Zarina (Fakulti Teknologi Maklumat dan Sains Kuantitatif, 2006)
E-Office consists of applications that support the administrative and management functions in the office. These include scheduling system, booking system and leave application. In Universiti Teknologi MARA (UiTM), the staff force consists of nearly 15,000 academic and non-academic employees in 22 faculties and administrative offices. Preliminary studies reveal that there are problems in administrating office tasks. These problems include poor retrieval of information, poorly organized office jobs, out-of-date or inaccurate information, misplaced and poorly designed forms as well as there being no confidentiality and privacy for applicants. Therefore, the requirement to implement e-office applications is highly critical. However, there have been no formal studies in requirement analysis for E-Office applications in this institution. Accurate understanding of the user requirement is essential, as it will determine the acceptance and its subsequent usage of e-office applications. Thus a survey was carried out amongst staffs to identify the user requirement for e-office applications that need to be implemented in UiTM. The analysis of the results shows that the majority of the respondents gave positive responses towards e-office implementation.